2006
DOI: 10.1038/sj.ijo.0803320
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a rapid weight loss induced by laparoscopic adjustable gastric banding on arterial stiffness, metabolic and inflammatory parameters in patients with morbid obesity

Abstract: Objective: To determine the effect of drastic weight loss on arterial compliance, inflammatory and metabolic parameters in patients with morbid obesity with and without cardiovascular risk factors who underwent laparoscopic adjustable gastric banding (LAGB). Design: Open prospective study, morbidly obese subjects divided into low-and high-risk group were evaluated before and 4 months after LAGB. Subjects: Forty-one Caucasian subjects aged between 16 and 55 years, with morbid (grade 3) obesity (20 low-risk and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 34 publications
2
17
1
2
Order By: Relevance
“…Our investigation corroborates preliminary studies (18,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) as it shows that obesity is a state of chronic low-grade inflammation and the weight reduction resulting from bariatric surgery significantly improves the inflammatory state. This amelioration relies on the continuous reduction in hs-CRP and IL-6 concentrations, associated with a parallel decrease in BMI.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our investigation corroborates preliminary studies (18,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) as it shows that obesity is a state of chronic low-grade inflammation and the weight reduction resulting from bariatric surgery significantly improves the inflammatory state. This amelioration relies on the continuous reduction in hs-CRP and IL-6 concentrations, associated with a parallel decrease in BMI.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have demonstrated that surgically induced weight loss is accompanied by an improvement of the endothelial function (18,19,21) and the proinflammatory state (18,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). However, few studies have studied endothelial function and proinflammatory state together, and have considered different time-points to determine postsurgical changes.…”
Section: Introductionmentioning
confidence: 99%
“…From prior studies, it appears that weight loss of >7% may improve arterial stiffness and BP. This amount of weight loss was also associated with improvement in lipid profile, inflammatory markers, and insulin sensitivity [7,22,37] achieved by a regimented nutritional and exercise intervention program [6]. Despite the improvement in hsCRP and insulin parameters, it is possible that the small weight loss achieved in this study and lack of improvement in lipid profile were not sufficient to improve arterial stiffness in our study.…”
Section: Discussioncontrasting
confidence: 45%
“…The association between changes in IL-6, insulin and HOMA after weight reduction have been found in some studies, [15][16][17]42 whereas Effect of body fat loss on inflammatory markers A Belza et al other studies have not found any relationships. 18,36,38,40 The general absence of correlation between change in hs-CRP and IL-6 and glycemic risk markers of IRS and CVD may be explained by an indirect relationship between the quantity of FM mass and the influence of energy balance, which seems to have a partial influence on concentration levels.…”
Section: Discussionmentioning
confidence: 99%
“…16,28,29,35,36 However, only hs-CRP and IL-6 were Figure 2 Loading plot of factor structure of the pro-inflammatory markers high-sensitive C-reactive protein (hs-CRP), interleukin-6 (IL-6), fibrinogen, haptoglobin, transferrin and the adipokines leptin and adiponectin. Factor 1 was related to fibrinogen (0.81), CRP (0.63), haptoglobin (0.71), IL-6 (0.64) whereas adiponectin, leptin and transferrin were not.…”
Section: Discussionmentioning
confidence: 99%